IMPROVEMENT OF THE TECHNOLOGY OF CASTING SHAFT COMPONENTS FROM 35XGCL BRAND STEEL IN AN ELECTRIC ARC FURNACE (American Journal of Interdisciplinary Research and Development, 2023)
In this article, 35XGCL steel alloy was liquidized. The resulting liquid metal is cleaned of non – metallic inclusions and gas pores by aluminum alloying, and casting technology was developed based on energy and resource efficient innovative technologies. In order to obtain a high – quality cast product, the composition of sand – clay and liquid glass mold mixtures was developed, and a high – quality cast product was liquefied. In addition, thermal treatment regimes were developed to increase the mechanical properties of the cast alloy, and as a result, a high – quality and resource – efficient cast product was obtained.